First report of Euthyneura (Heterobranchia: Gastropoda) in the Early Jurassic of Southern Patagonia, Argentina - Ferrari, Silvia Mariel (2023)
The present paper aims at the description of two new species of Euthyneura (Heterobranchia: Gastropoda) in the Early Jurassic (early Pliensbachian) marine deposits of the Chubut Basin at southern Patagonia, Argentina. The new species Cossmannina australis nov. sp. and Cylindrobullina caquelensis nov. sp. were found at the Cerro Caquel locality located in the western slope of Sierra de Tecka and río Tecka valley. The new locality yielded the ammonite Eoamaltheus sp. (E. meridianus Hillebrandt Zone, upper part of Ibex Zone to Davoei Zone) which allowed to assign an early Pliensbachian age for the marine deposits at the studied area, providing also new evidence of the oldest record within the Early Jurassic in the Sierra de Tecka region. The new report of Euthyneura in the Chubut Basin extends the palaeobiogeographical distribution of this clade into the southern hemisphere during the earliest Pliensbachian.